2013
DOI: 10.1038/ncomms2337
|View full text |Cite
|
Sign up to set email alerts
|

High current superconductivity in FeSe0.5Te0.5-coated conductors at 30 tesla

Abstract: Although high-temperature superconductor cuprates have been discovered for more than 25 years, superconductors for high-field application are still based on low-temperature superconductors, such as Nb(3)Sn. The high anisotropies, brittle textures and high manufacturing costs limit the applicability of the cuprates. Here we demonstrate that the iron superconductors, without most of the drawbacks of the cuprates, have a superior high-field performance over low-temperature superconductors at 4.2 K. With a CeO(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
203
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(222 citation statements)
references
References 26 publications
16
203
2
1
Order By: Relevance
“…On the other hand, its simple structure and less toxic nature are also preferable for fabricating wires and thin films, although the critical current density, J c , in FeTe 0.5 Se 0.5 bulks and wires [6,7] is still much lower than that of the Ba 0.6 K 0.4 Fe 2 As 2 wires [8]. Our previous reports have demonstrated that high-quality FeTe 0.5 Se 0.5 thin films can maintain a large J c over 10 6 A/cm 2 at 4.2 K. Even under the field of 30 T, J c 's are still exceeding 10 5 A/cm 2 [9,10]. For the practical application of superconducting wires and tapes, local characterizations of J c distribution are very important.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, its simple structure and less toxic nature are also preferable for fabricating wires and thin films, although the critical current density, J c , in FeTe 0.5 Se 0.5 bulks and wires [6,7] is still much lower than that of the Ba 0.6 K 0.4 Fe 2 As 2 wires [8]. Our previous reports have demonstrated that high-quality FeTe 0.5 Se 0.5 thin films can maintain a large J c over 10 6 A/cm 2 at 4.2 K. Even under the field of 30 T, J c 's are still exceeding 10 5 A/cm 2 [9,10]. For the practical application of superconducting wires and tapes, local characterizations of J c distribution are very important.…”
Section: Introductionmentioning
confidence: 99%
“…21 On the other hand, its relatively low T c is also meaningful to understand the crossover between HTS and low temperature superconductors, and to examine the validity of vortex-related theory in a much broader temperature range.…”
mentioning
confidence: 99%
“…However, the overriding application metric, the maximum loss-less electrical current density, is ultimately determined by the vortex pinning that can be engineered into the material. Significant advances towards highperforming superconducting materials based on the so-called 122-compounds, most notably Ba(Fe 1 À x Co x ) 2 As 2 and Ba 1 À x K x Fe 2 As 2 (refs 6-8), and 11-compounds 9 have been made. For instance, Ba 0.6 K 0.…”
mentioning
confidence: 99%